Perbedaan Strategi Pemasaran Standar vs Lokal (Standardization vs Localization) - Chesta Fillail Adabi (PUTRA JAWA PUBLISHER, 2024)
Advertising is an important element in the formation of values that will shape cultures and behaviors that ultimately determine people's consumption patterns. Advertising is now a powerful weapon for globalized companies to market their products to the world network and form a new era of colonization